Parental migration and self-reported health status of adolescents in China: A cross-sectional study. (May 2020) - Lu, Weijia; Zhang, Anwen; Mossialos, Elias
Abstract: Background: Over 100 million children are parented by migrant workers in China. The aim of this study was to investigate how self-reported adolescent physical and mental health are associated with parental migration. Methods: Based on cross-sectional data of 13996 students in 112 schools drawn from a nationally representative sample of middle school students in China, this study used self-reported measures for adolescent physical and mental health. Ordered logistic regression was used for the analysis of self-reported physical health, and linear regression was used for the analysis of self-reported mental health, both adjusting for socio-economic covariates and school fixed effects, to determine how adolescent health is associated with parental migration. Findings: In urban areas, migrant adolescents were physically healthier (OR=1.19, 95% CI: 1.03–1.36), and similarly mentally healthy ( b =-0.07, 95% CI: -0.37–0.23), compared to urban adolescents from intact families; in rural areas, left-behind adolescents were less physically (OR=0.84, 95% CI: 0.76–0.94) and mentally ( b =0.45, 95% CI: 0.24–0.66) healthy than rural-intact adolescents, holding other variables constant. Left-behind adolescents had less close parent-adolescent relationships than rural-intact adolescents with both father (OR=0.63, 95% CI: 0.56–0.71) and mother (OR=0.62, 95% CI: 0.54–0.70). Interpretation: Our study highlights a great need for health interventions aimed at left-behind adolescents in China and globally, and the important roles of parent-adolescent relationships in addressing the health needs of left-behind adolescents.